2014
DOI: 10.1158/0008-5472.can-14-0819
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer–Specific Cell Death Induced In Vivo by Cytoplasmic-Delivered Polyinosine–Polycytidylic Acid

Abstract: Polyinosine-polycytidylic acid (pIC) is a synthetic dsRNA that acts as an immune agonist of TLR3 and RLR to activate dendritic and NK cells that can kill tumor cells. pIC can also trigger apoptosis in pancreatic ductal adenocarcinoma cells but its mechanism of action is obscure. In this study, we investigated the potential therapeutic activity of a formulation of pIC with polyethylenimine ([pIC]PEI) in PDAC and investigated its mechanism of action. [pIC]PEI stimulated apoptosis in PDAC cells without affecting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“…Furthermore AKT seems to be able to influence directly the immune resistance of malignant cells e.g. ovarian tumour cells [73,95,[129][130][131]. Comparison of parental and immuneresistant ovarian tumours revealed that AKT is highly activated in the immune-resistant tumours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore AKT seems to be able to influence directly the immune resistance of malignant cells e.g. ovarian tumour cells [73,95,[129][130][131]. Comparison of parental and immuneresistant ovarian tumours revealed that AKT is highly activated in the immune-resistant tumours.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, there is accumulating evidence that the PI3K/AKT/mTOR pathway is involved in the development of several malignant traits of cancer cells as well as their escape from immunity [128]. In some studies the interactions between cancer cells and natural-killer (NK)-cells have been enlightened [73,95,[129][130][131]. Modified FATAL assay was used for determining the killing efficiency of NK-cells in regard to ovarian cancer cell models in-vitro.…”
Section: Role Of Akt Expression Level In Tumour Cells In Regard To Nkmentioning
confidence: 99%
“…Adapted from Quinn et al (2015). (Ammi et al, 2015;Bhoopathi et al, 2014). TLRs act as primary sensors, recognizing innate patterns of bacterial or viral infection (Barral et al, 2009).…”
Section: Poly I:cmentioning
confidence: 99%
“…Through these pathways, pIC can directly activate dendritic cells and promote NK cells to attack tumors by mimicking viral RNA (Perrot et al, 2010). While pIC has been utilized extensively in clinical trials (Gnjatic, Sawhney, & Bhardwaj, 2010), only recently has the mechanism of action in pancreatic cells been uncovered (Bhoopathi et al, 2014). pIC exposure induces elevated levels of proteins involved in viral and tumoral host defenses, including type I IFNs, OAS, RIG-I helicase, and MDA-5 (Barral et al, 2009;Gnjatic et al, 2010).…”
Section: Poly I:cmentioning
confidence: 99%
See 1 more Smart Citation